Reflections on setting up a nursing preceptorship programme. (11th June 2020) - Baldwin, Sharin; Coyne, Tracey; Hynes, Claire; Kelly, Patricia
Abstract : It is now common practice for preceptorship programmes to be offered to newly qualified nurses within the NHS. The Nursing and Midwifery Council expects newly qualified nurses to be given protected time for learning in their first year of qualified practice and to access support from a preceptor. This article discusses a preceptorship programme that has been implemented in a large integrated NHS Trust in north-west London and shares reflections and learning to date, which can benefit others wanting to roll out a similar programme in the UK.